Regulation of cAMP-dependent protein kinases: the human protein kinase X (PrKX) reveals the role of the catalytic subunit alphaH-alphaI loop. - Diskar, M; Zenn, H; Kaupisch, A; Kaufholz, M; Brockmeyer, S; Sohmen, D; Berrera, M; Zaccolo, M; Boshart, M; Herberg, F; Prinz, A (2010)
cAMP-dependent protein kinases are reversibly complexed with any of the four isoforms of regulatory (R) subunits, which contain either a substrate or a pseudosubstrate autoinhibitory domain. The human protein kinase X (PrKX) is an exemption as it is inhibited only by pseudosubstrate inhibitors, i.e. RIα or RIβ but not by substrate inhibitors RIIα or RIIβ. Detailed examination of the capacity of five PrKX-like kinases ranging from human to protozoa (Trypanosoma brucei) to form holoenzymes with human R subunits in living cells shows that this preference for pseudosubstrate inhibitors is evolutionarily conserved. To elucidate the molecular basis of this inhibitory pattern, we applied bioluminescence resonance energy transfer and surface plasmon resonance in combination with site-directed mutagenesis. We observed that the conserved αH-αI loop residue Arg-283 in PrKX is crucial for its RI over RII preference, as a R283L mutant was able to form a holoenzyme complex with wild type RII subunits. Changing the corresponding αH-αI loop residue in PKA Cα (L277R), significantly destabilized holoenzyme complexes in vitro, as cAMP-mediated holoenzyme activation was facilitated by a factor of 2-4, and lead to a decreased affinity of the mutant C subunit for R subunits, significantly affecting RII containing holoenzymes.